2020
DOI: 10.1002/jbmr.4253
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk Between Histone and DNA Methylation Mediates Bone Loss in Hind Limb Unloading

Abstract: Bone loss induced by mechanical unloading is a common skeletal disease, but the precise mechanism remains unclear. The current study investigated the role of histone methylation, a key epigenetic marker, and its cross‐talk with DNA methylation in bone loss induced by mechanical unloading. The expression of G9a, ubiquitin‐like with PHD and ring finger domains 1 (UHRF1), and DNA methylation transferase 1 (DNMT1) were increased in hind limb unloading (HLU) rats. This was accompanied by an increased level of histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…For disuse osteoporosis, there are few studies on ferroptosis and its related mechanisms and biomarkers. Recent studies found that the upregulation of DNA methylation-related DNMT1 and histone methylation-related EHMT2 genes would cause disused osteoporosis [ 25 ]. Past studies based on GSE100933 found that GSNAS1, SNHG12, and EPB41LA4A-AS1 can be seen as potential regulators in disuse osteoporosis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For disuse osteoporosis, there are few studies on ferroptosis and its related mechanisms and biomarkers. Recent studies found that the upregulation of DNA methylation-related DNMT1 and histone methylation-related EHMT2 genes would cause disused osteoporosis [ 25 ]. Past studies based on GSE100933 found that GSNAS1, SNHG12, and EPB41LA4A-AS1 can be seen as potential regulators in disuse osteoporosis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…mRNA extraction and qRT-PCR were performed as previously described [ 32 ]. Total RNA was isolated from fresh-frozen thyroid cancer tissues and thyroid cancer cell lines using TRIzol reagent (Invitrogen, Carlsbad, USA) and reverse-transcribed to cDNA using PrimeScript RT Master (Takara, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…QPCR was carried out using ChamQ Universal SYBR qPCR Master Mix (Vazyme) and mRNA expressions were normalized to reference genes GAPDH. The primers used in all qPCR assays are listed in Additional file 1 : Table S1 [ 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%